2014
DOI: 10.1007/s00261-014-0076-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive detection of infection in acute pancreatic and acute necrotic collections with diffusion-weighted magnetic resonance imaging: preliminary findings

Abstract: DW-MRI can be used as a non-invasive technique for the detection of infection in acute pancreatitis-associated collections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 34 publications
1
23
0
1
Order By: Relevance
“…This will allow definitive proof of infection in the majority of patients. Preliminary experience with diffusion-weighted magnetic resonance imaging for the non-invasive detection of infection in acute pancreatic and acute necrotic collections is promising and requires further evaluation [16]. Given that it is unusual to alter clinical management on the basis of the diagnosis of necrosis per se, it may be more important to focus on developing an accurate approach to diagnosing infected necrosis.…”
Section: Local Complicationsmentioning
confidence: 96%
“…This will allow definitive proof of infection in the majority of patients. Preliminary experience with diffusion-weighted magnetic resonance imaging for the non-invasive detection of infection in acute pancreatic and acute necrotic collections is promising and requires further evaluation [16]. Given that it is unusual to alter clinical management on the basis of the diagnosis of necrosis per se, it may be more important to focus on developing an accurate approach to diagnosing infected necrosis.…”
Section: Local Complicationsmentioning
confidence: 96%
“…[30][31][32][33][34] MR is more sensitive than CT for detecting hemorrhage and for demonstrating communication of a collection with the pancreatic duct. Although MR with diffusion-weighted sequences may be equivalent to iodinated contrast material-enhanced CT for the diagnosis of acute pancreatitis, it is superior to nonenhanced CT. 34 For complete evaluation of the pancreatic duct and parenchyma, the following sequences are used at the University of California, San Francisco: in-phase and opposed-phase T1-weighted gradient echo in the axial plane, T2-weighted single-shot fast spin echo or turbo spin echo in the axial and coronal plane, T2-weighted fast recovery spin echo with fat suppression in the axial plane, and T1-weighted, 3-dimensional dynamic gradient echo before and after gadolinium with fat suppression in the axial plane.…”
Section: Magnetic Resonancementioning
confidence: 99%
“…Diffusion-weighted MR imaging is added because it enables differentiation between different degrees of severity of acute pancreatitis and between sterile and infected collections associated with acute pancreatitis. 33,34 Heavily T2-weighted MRCP sequences may be added when needed as a slab or 3-dimensional technique in the coronal plane. Because MR protocols are persistently evolving, the details are not listed here.…”
Section: Magnetic Resonancementioning
confidence: 99%
“…The utility of DWI is under investigation, and it has been suggested that central portions of infected acute peripancreatic fluid collections and acute necrotic collections exhibit more restricted diffusion compared with their sterile counterparts, although overlap may be seen [77,78]. When infection is suspected, aspiration of fluid for culture is necessary [75].…”
Section: Secondary Infectionmentioning
confidence: 99%